2019
DOI: 10.1080/17461391.2019.1674926
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing the measurement of expectations to better understand placebo and nocebo effects in psychological responses to exercise

Abstract: The understanding of placebo and nocebo effects in psychological responses to exercise may be improved by measuring expectations. Despite availability of several validated expectation measures, we argue for using scales that take both positive and negative expectations for exercise-induced changes into account. A cross-sectional survey was used to collect information on positive and negative expectations pertaining to how exercise would affect 14 different outcomes related to psychological health (n = 966). Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The fact that there was no difference in speed in the trials (for both placebo and nocebo) between those who reported a difference in the speed and those who could not feel a difference shows that the subjective experience in speed is a result of the false belief and expectation of the participants before the trial, rather than the speed they actually achieved during the trial. These findings are in line with other recent research on how expectations can modulate placebo and nocebo effects 16 . giving athletes a certain belief about their equipment will modify their anticipation about the outcome of the performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fact that there was no difference in speed in the trials (for both placebo and nocebo) between those who reported a difference in the speed and those who could not feel a difference shows that the subjective experience in speed is a result of the false belief and expectation of the participants before the trial, rather than the speed they actually achieved during the trial. These findings are in line with other recent research on how expectations can modulate placebo and nocebo effects 16 . giving athletes a certain belief about their equipment will modify their anticipation about the outcome of the performance.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with other recent research on how expectations can modulate placebo and nocebo effects. 16 giving athletes a certain belief about their equipment will modify their anticipation about the outcome of the performance. Athletes with a positive belief about their equipment will anticipate a better outcome compared to athletes that have a negative belief.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, expectations of the health effects of exercise can have powerful effects on health outcomes, thus the different findings for occupational versus leisure-time physical activity may have been the result of different expectations. 47 Many people expect leisure-time physical activity to improve psychological well-being and other health outcomes, 48 but there is evidence that people lack those same expectations about occupational physical activity. 49…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the blinding of participants in exercise studies is exceedingly difficult because the participants notice if they are exercising or not. To minimize the risk of bias arising from not blinding participants (e.g., due to expectation effects), it is recommended that future studies should control appropriately for confounders, for instance, by assessing additional biopsychosocial variables (e.g., sleep, level of arousal, mood) [114][115][116][117][118] and/or a placebo group [116] (e.g., the placebo [sham] group performs the same exercise but without loading [119,120] or an inadequate dose to induce considerable effects [121]) when possible. Furthermore, with respect to the domain of "other bias", we recommend that upcoming studies pay stronger attention to developing a more rigorous study design (see the next Section 4.2, Study characteristics, for a detailed discussion, as well as Figure 4) [33] and better exercise prescription (see Section 4.3, Exercise characteristics, for a detailed discussion).…”
Section: Risk Of Biasmentioning
confidence: 99%